Development of an equivalent system frequency response model based on aggregation of distributed energy storage systems - Duan, Shuyin; Zhang, Jinjia; Yu, Lei; Cai, Zexiang (Frontiers in Energy Research, 2024)
Energy Storage Systems (ESS) installed in distribution networks have been widely adopted for frequency regulation services due to their rapid response and flexibility. Unlike existing ESS designing methods focusing on control strategies, this paper proposes a new method based on ESS equivalent aggregated model (EAM) for calculating the capacity and the droop of ESS to maintain system frequency nadir and quasi-steady state frequency using low-order functions.The proposed method (i) uses first-order functions to describe the frequency response (FR) of synchronous generators (SGs), (ii) ignores the control strategies of SGs, making the method systematic and allowing it to avoid analyzing complex high-order functions and (iii) is suitable for low inertia systems. The applicability and accuracy of the method is demonstrated using a modified four-generator two-area (4G2A) system.